2020
DOI: 10.1111/phpp.12538
|View full text |Cite
|
Sign up to set email alerts
|

Role of 904 nm superpulsed laser‐mediated photobiomodulation on nitroxidative stress and redox homeostasis in burn wound healing

Abstract: BackgroundBurn wound healing is delayed due to several critical factors such as sustained inflammation, vascular disorder, neuropathy, enhanced proteolysis, infection, and oxidative stress. Burn wounds have limited oxygen supply owing to compromised blood circulation. Hypoxic burn milieu leads to free radicals overproduction incurring oxidative injury, which impedes repair process causing damage to cell membranes, proteins, lipids, and DNA. Photobiomodulation (PBM) with 904 nm superpulsed laser had shown poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Furthermore, reactive oxygen species (ROS) are produced in response to cutaneous injury, and act as cellular messengers to stimulate several physiological processes, such as cytokine action, cell motility and angiogenesis [ 4 ]. However, cutaneous injury affects the healing process by the overproduction of ROS and the perturbation of various enzymatic and non-enzymatic antioxidant defenses [ 6 ], particularly during the inflammatory phase [ 7 ]. Long-term instability and high concentration of ROS may cause cellular injury by damaging both proteins and membrane lipids, the perturbation of antioxidant enzymes and the breakdown of the nucleic acids, particularly DNA [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reactive oxygen species (ROS) are produced in response to cutaneous injury, and act as cellular messengers to stimulate several physiological processes, such as cytokine action, cell motility and angiogenesis [ 4 ]. However, cutaneous injury affects the healing process by the overproduction of ROS and the perturbation of various enzymatic and non-enzymatic antioxidant defenses [ 6 ], particularly during the inflammatory phase [ 7 ]. Long-term instability and high concentration of ROS may cause cellular injury by damaging both proteins and membrane lipids, the perturbation of antioxidant enzymes and the breakdown of the nucleic acids, particularly DNA [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Associated with these effects, some studies report the potential of PBM to significantly reduce the levels of reactive oxygen species, as well as promote a protective action against oxidative damage, evidenced by the reduction in protein carbonylation. 68 A study by Silveira 69 observed a significant reduction in oxidative damage and the production of reactive species after laser irradiation, which indicates that PBM helps in the modulation of oxidative stress; an effect attributed to its ability to restore the mitochondrial membrane potential to baseline, and thereby reduce the generation of ROS in cells with oxidative stress. 70…”
Section: Discussionmentioning
confidence: 99%
“…67 Associated with these effects, some studies report the potential of PBM to significantly reduce the levels of reactive oxygen species, as well as promote a protective action against oxidative damage, evidenced by the reduction in protein carbonylation. 68 A study by Silveira 69 observed a significant reduction in oxidative damage and the production of reactive species after laser irradiation, which indicates that PBM helps in the modulation of oxidative stress; an effect attributed to its ability to restore the mitochondrial membrane potential to baseline, and thereby reduce the generation of ROS in cells with oxidative stress. 70 The excess of free radicals and the exacerbated inflammatory response generate changes in tissue histoarchitecture that hinder the formation of new tissue, due to this, through the histological analysis of the integumentary system, we evaluated the average number of inflammatory infiltrates (Figure 8(b)), from fibroblasts (Figure 8(c)), and compaction of collagen fibers (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 7(d)) LPO is the product of lipid peroxidation, which is usually related to free radical damage. 55 LPO is formed by lipid peroxidation of polyunsaturated fatty acids and other molecules in the biofilm, which causes cell damage and destroys the normal structure and function of the cell membrane and other organelles. 56 These results suggest that the degree of oxidative stress in the wound is reduced after the application of CPPM, thus improving wound healing.…”
Section: Resultsmentioning
confidence: 99%